INITIATED PENALTIES FOR CORRUPT BEHAVIOR IN A SOCIOLOGICAL PERSFEKTIF - Haling, Syamsul (Journal of Humanity, 2016)
Sociological persfektif in many social sanctions bid can be applied in corruptbehavior pananggulangan. The idea of social sanctions were proposed as a reactionagainst the growing number of corrupt behavior difficult resolved only throughnational and international legal instruments. It is time the exact type of sanctions werefound to tackle corrupt behaviour that are already classified as extraordinary crimes.Some ideas proposed as social sanctions to eradicate corrupt behavior i.e. criminalsanctions established on the basis of social stratification, pencemohan self and familycorruptor, no corpse mensholatkan corruptor before is no guarantee of the financialreturns of the State by the family of the perpetrator, serving in the corruptors facetelivisi and penalties for disseminating the corruptor after death and as sanctionsultimium remidium every corruptor will be charged all his deeds before God afterdeath.